1996
DOI: 10.1073/pnas.93.7.3056
|View full text |Cite
|
Sign up to set email alerts
|

Successful expression of human factor IX following repeat administration of adenoviral vector in mice.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 20 publications
4
79
1
Order By: Relevance
“…Administration of adenovirus vectors into the trachea, skeletal muscle, thoracic cavity or vasculature of neonatal mice or rats results in transgene expression for several weeks or months. 12,13,[18][19][20][21][22] Subsequent administration of the adenovirus vectors were tolerated and resulted in robust gene expression in some studies 19,20,23 but not others. 18 The relative success of this approach in rodents has been attributed to the relative immaturity of the immune system in the rodent at birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of adenovirus vectors into the trachea, skeletal muscle, thoracic cavity or vasculature of neonatal mice or rats results in transgene expression for several weeks or months. 12,13,[18][19][20][21][22] Subsequent administration of the adenovirus vectors were tolerated and resulted in robust gene expression in some studies 19,20,23 but not others. 18 The relative success of this approach in rodents has been attributed to the relative immaturity of the immune system in the rodent at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in neonatal mice and rats have demonstrated that priming with an initial intravenous dose of adenovirus vector resulted in tolerance to subsequent administration of the same vector. 19,23 The intravenous route, which delivers …”
Section: Discussionmentioning
confidence: 99%
“…29,30 This new system has the theoretical advantage ence with adenoviral vectors is mainly a function of the immunogenicity of adenoviral proteins. 23,27 However, of eliminating possible viral protein-mediated immunogenicity. Factors contributing to lack of persistence will more recent data show that the expressed transgene carried by the adenoviral vector is the major immunogen.…”
Section: Figure 4 Comparison Of Multiple Rh-leptin Daily Injections Wmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14] Their immunogenicity has been exploited to study the possibility of fetal immune tolerance after prenatal administration. [15][16][17] However, loss of these episomal DNA vectors during subsequent cell divisions following infection severely curtails their applicability to long-term fetal gene therapy.…”
Section: Introductionmentioning
confidence: 99%